The Citibank India story: Nurturing global leaders - LUTHRA, Poornima (Institutional Knowledge at Singapore Management University, 2015)
It is August 2014, and the Citibank conference on leadership and development has just concluded. Immediately after, Sara Roberts, Talent Head of Citigroup Asia Pacific, and Anuranjita Kumar, Chief Human Resource Officer (CHRO) of Citigroup South Asia, sit together in the coffee shop of Mumbai’s Taj Hotel to discuss a pressing issue: how talent and development programmes at Citibank India could evolve to cultivate the bank’s future leaders. Citibank India has nurtured multiple leaders within its ranks throughout the 80’s and through to the early 2000’s, who have gone on to take up top leadership positions in the global banking industry. Roberts and Kumar interview six Citibank veteran business leaders in this regard – five of them have over 20 years’ experience with the bank, whereas four members of the group have been with Citibank India for more than ten years. Their feedback shows that the culture is largely meritocracy-based and performance-driven. Employees are developed through both formal and informal structures and networks. There are also structured training programmes that provide very strong organisational support to build hard and soft skills early on in an employee’s career and later at key career transition points. By the beginning of the 21st century, Citibank India has grown to become a much larger organisation with roles requiring increased specialisation. Compared to the 80’s and 90’s, India’s business environment has become far more competitive, faster paced and heavily influenced by technology. The younger generation of new hires who are born in the 80’s and early 90’s (the Gen Y cohort) has a different set of career expectations and aspirations. It becomes apparent there is a need to create new initiatives to foster the development of the future leaders of Citibank India, and Roberts and Kumar are preparing for it.